Resonance states near a quantum magnetic impurity in single-layer FeSe superconductors with d-wave symmetry. (5th July 2018) - Chen, Liang; Zhao, Wei-Wei; Han, Rong-Sheng
Abstract: In this work, we investigate the local density of states (LDOS) near a magnetic impurity in single-layer FeSe superconductors. The two-orbital model with spin–orbit coupling proposed in Agterberg et al (2017 Phys. Rev. Lett .119 267001) is used to describe the FeSe superconductor. In the strong coupling regime, two impurity resonance peaks appear with opposite resonance energies in the LDOS spectral function. For strong spin–orbit coupling, the superconducting gap in this model is d -wave symmetric with nodes, the spatial distributions of the LDOS at the two resonance energies are fourfold symmetric, which reveals typical characteristic of d -wave pairing. When the spin–orbit coupling is not strong enough to close the superconducting gap, we find that the spatial distribution of the LDOS at one of the resonance energies manifests s -wave symmetry, while the pairing potential preserves d -wave symmetry. This result is consistent with previous experimental investigations.